A Limited Central Bank. Issue 4 (21st November 2019) - Plosser, Charles I.
Abstract : The President of the Philadelphia Federal Reserve Bank from 2006–2015 discusses the Fed's essential role as preserver of the currency's purchasing power and how the institution might be improved to better fulfill that role. To that end, the author proposes the imposition of four limits on the central bank that, by restricting its discretion, can be expected to improve outcomes and accountability. First, limit the Fed's monetary policy goals to a narrow mandate in which price stability is the sole, or at least the primary, objective; Second, limit the types of assets that the Fed can hold on its balance sheet to Treasury securities; Third, limit the Fed's discretion in monetary policymaking by requiring a systematic, rule‐like approach; and Fourth, limit the boundaries of its lender‐of‐last‐resort credit extension. These changes, by creating a more limited central bank, would help preserve the central bank's independence, thereby improving the effectiveness of monetary policy. They would also make it easier for the public to hold the Fed accountable for its policy decisions.